GRAFTING OF CELLULOSIC PALMITATE-METHYL METHACRYLATE BY ELECTRON BEAM IRRADIATION AND CHARACTERIZATION OF THEIR MEMBRANES MECHANICAL PROPERTIES - Asep Riswoko; Tri Suryanti (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
GRAFTING OF CELLULOSIC PALMITATE-METHYL METHACRYLATE BY ELECTRON BEAM IRRADIATION AND CHARACTERIZATION OF THEIR MEMBRANES MECHANICAL PROPERTIES. A cellulose derivative membrane, cellulosic palmitate, has been modified to give a better mechanical properties of composite membranes. Modification has been carried out by adding methyl methacrylate (MMA) onto cellulosic palmitate with volume ratio 1:1 and then irradiated by electron beam at dosage of 3, 5, 7, 9, and 10 kGy. The best performance of MMA grafted cellulosic membrane was successfully obtained for irradiation dose at 5 kGy which has a tensile strength of 76,92 Kg/cm2 (stronger than that of the original cellulosic palmitate membrane up to 75%). This result is supported by FT-IR spectra which showed that grafting methyl methacrylate onto cellulosic palmitate increased the intensity of absorbance of -CH2- group (1468.47 and 1450.47 cm-1). In addition, there are also strong absorption in region 1068.64 and 1014.56 cm-1 which is absorption for C-O-C (ether linkage) between cellulosic palmitate and methyl methacrylate. X-Ray Diffraction and SEM analysis were also revealed that adding of MMA on cellulosic palmitate affected a degree of crystalline and morphology membrane.